2017
DOI: 10.4103/ijmpo.ijmpo_115_17
|View full text |Cite
|
Sign up to set email alerts
|

The role of mutation testing in patients with chronic myeloid leukemia in chronic phase after imatinib failure and their outcomes after treatment modification: Single-institutional experience over 13 years

Abstract: Introduction:BCR-ABL1 kinase domain mutations represent the most frequent mechanism of resistance to tyrosine kinase inhibitor (TKI) therapy, being detected in 40%–50% of imatinib-resistant patients with chronic myeloid leukemia in chronic phase (CML-CP). Over 100 BCR-ABL1 single-point mutations have been reported in patients with imatinib-resistant CML. There were few studies reported from India on BCR-ABL kinase mutations in imatinib failure patients. We present our data on imatinib resistance mutation analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…This is in corroboration with previous Indian patient reports by Chaitanya et al 16 and Rajappa et al 15 describing TKD mutations in 33 and 29% CML patients, respectively. Overall, the incidence of TKD mutation has been reported in 30 to 50% imatinib-intolerant patients worldwide.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is in corroboration with previous Indian patient reports by Chaitanya et al 16 and Rajappa et al 15 describing TKD mutations in 33 and 29% CML patients, respectively. Overall, the incidence of TKD mutation has been reported in 30 to 50% imatinib-intolerant patients worldwide.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, the incidence of TKD mutation has been reported in 30 to 50% imatinib-intolerant patients worldwide. 27 28 29 30 Gender distribution of the present cohort is comparable to Chandrasekhar et al, 2 Tripathi et al, 7 and Chaitanya et al 16 but is significantly different from Patkar et al 19 and Rajappa et al 15 We also observe a slightly higher median age in comparison to other studies ( Table 2 and 4 ). In addition, treatment resistant cases that harbored a mutation ( n = 236) in the BCR-ABL1 KD show that the female gender has a markedly lower presentation of resistant mutations suggesting alternative mechanisms that may possibly be contributing to their suboptimal response to therapy.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Numerous studies have reported on the frequency of secondary mutations following treatment with type II inhibitors. Although the rankings of mutation frequencies may vary slightly, the gatekeeper mutation T315I consistently emerges as the most frequent mutation after imatinib treatment. For quizartinib, mutations associated with the D835 residue in the A-loop are prevalent. , Notably, mutations at these two locations pose significant challenges for type II inhibitors to overcome and require specific efforts from medicinal chemists. ,, …”
Section: Conclusion and Perspectivementioning
confidence: 99%